Landslides and Sounds due to Earthquakes In relation to the Upper Atmosphere (MAUSAM, 1952)
A survey is made of' landslides ' and' explosive sounds' associated with violent tectonic earthquakes which occurred in India and neighbourhood during the past one and a quarter century, with special reference to the very large earthquake of 1950. Results of allied studies made elsewhere, are reviewed.‘Earthquake sounds’ originate in the focal regions of the disturbances, travel in the rock with the speed of elastic waves and after refraction into the air, proceed at a very small angle with the vertical. However loud, such waves cannot return to the ground to be audible at any large distance from the place of emergence from the ground.. Explosive Bounds heard at large distances from the epicentres long aft3r the earthquakes, are produced by landslides. They travel at small angles with the horizontal. After a detour of the upper atmosphere these Bounds can return to the ground and, by successive recurvatures in the upper air and reflections on the ground, can be audible at different distant zones of audibility. The explosive sounds due to submarine earthquakes, like the, Barlsal guns" appear to owe their origin to some volcanic phenomenon, either in association with the earth-quakes or initiated by their effect elsewhere, Audibility of these Bounds at large distances can then be explained by abnormal propagation through the upper atmosphere. By an analysis of the observed elements of sounds and various characteristics of the earthquakes and by comparison with the results of explosion-natural and experimental inferences are made regarding the time and place of occurrence and the number and dimensions of landslides relating to the sounds. Travel times of abnormal sounds, due to earthquakes in India, are thus obtained and these afford a means of Obtaining the temperature of the upper atmosphere, the form of trajectory and critical speed of sound. Preliminary examination shows that these results are approximately in agreement with those obtained from the' explosion' experiments made in India during 1946.47.The study emphasises the need for re-organising the existing system of voluntary observations of earthquakes.